Online Platform for Matching and Trading Shares of Autonomous Vehicles. Issue 3 (March 2022) - Allahviranloo, Mahdieh; Bouyeure, Coline
In this paper, an online platform for a system of shared autonomous vehicles (AVs) is designed and tested. A model of fractional ownership among different households is presented, and a one-sided many-to-many matching problem between households and vehicles is solved. Preferences over vehicles, demographics of other co-owners, and weekly activity patterns of households are key factors taken into account in the matching process. In the designed platform, co-owners of each vehicle can reserve the vehicle in advance and can trade the reserved time with the other co-owners if the vehicle is no longer needed. Real-time submission of requests can also be accommodated through a trading mechanism among co-owners. The proposed architecture of the platform consists of three main components: ( i ) a web-based user interface, ( ii ) database, and ( iii ) backend computation. The platform was tested using data collected from 15 households, who entered their trips and trading requests into the system.